Understanding the current practice of conserving heritage building in Malacca - Hasif Rafidee Hasbollah; Mohd Firdaus Mahamad Ali (Universiti Malaysia Kelantan, 2015)
Conserving a heritage building can be daunting. This developing study seeks to understand the current practice of conserving a heritage building in the historic city of Malacca. A series of eight sessions of interviews withexperts were conducted at three levels of conservation practitioners at the strategic, tactical, and operational levels in Malacca, the World Heritage City. At strategic level, which is the first level, is known to associate with the long-range aims and direction of the organisation’s functions of conservation work in Malaysia. Secondly, the tactical or managerial level, which is concerned with delivering the totality of functions of the conservation work in Malaysia. Thirdly, at the operational level, which is responsible for the periodic and conservation maintenance work operations. The respondents perceived that all Cultural Values which are social, historic, aesthetic, scientific, and ecological have been used as the current practice in conserving heritage buildings in Malaysia. Thence, these conservation practitioners have stated that they have been applying Cultural Values which are in accordance with four vital documents which are “The National Heritage Act of Malaysia”, “Outstanding Universal Values by UNESCO”, and “The Guidelines for Conservation of Heritage Building” and “The Conservation Management Plan of Malacca” in conservation works in Malaysia. Hence, understanding the overview of current practice of conservation practitioners can draw the development characteristics that led to the robust model of conservation in Malaysia